Islam and Spiritual Health - Najwa Khairina; Nur Romdhona; Rohimi Zamzam; Dina Rahma Fadlilah; Sari Suriani (Indonesian Journal of Islam and Public Health, 2021)
Humans are divine beings, who need spiritual fulfillment, and the most important thing is to be able to live and practice their religious teachings in order to obtain strength and tranquility in life. Spiritual health is about trying to live with a whole person. This is a process that must be carried out in the course of life. When spirituality is healthy and balanced, the power to commit wrongdoing will decrease and balance in life will be fulfilled. Spiritualism in religion is belief. There is a strong emotional involvement, both in rejection and acceptance of this spiritualism. Spirituality is closely related to other dimensions and can be achieved if there is a balance with other dimensions (physiological, psychological, sociological, cultural). Spiritual is very influential on individual's coping. The higher the spiritual level of an individual, the coping possessed by that individual will also increase. So that it can increase the adaptive response to the various changes that occur in these individuals